Beyond Food Delivery : The Role of Core Business and Other Success Factors for Superapps, Lessons from Grab's SEA Dominance for Wolt's Expansion in the Czech Republic - Budinský, Jan; Kopkáně, Heřman; Machek, Ondřej, 1985-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2024)
This thesis delves into the multifaceted world of super apps, all-in-one platforms offering a variety of services integrated into a single application, which are revolutionizing the field of global mobile apps. A multilateral approach sheds light on their current landscape, history, and future trajectory. A comprehensive overview details super app benefits, challenges, and successful examples. Logistic regression models written in R using RStudio analyze data from five key industries (Mobility, Food Delivery, Messaging, Fintech, and eCommerce) to identify factors influencing the adoption of super app strategies and address the limited research on super apps outside the Mobility sector. Analysis of 1783 companies, identifying 43 as super apps, reveals that significant funding, regional origin, and company size are crucial determinants. A survey of 104 respondents from 36 countries explores user awareness, and usage patterns, bridging the knowledge gap on super app consumer preferences and revealing a significant discrepancy between usage and awareness of these platforms. Additionally, a descriptive analysis of Grab’s success offers strategic insights into Wolt’s potential super app journey in the Czech market. All these findings provide a complex understanding of the super app phenomenon and offer valuable learnings and inspiration for researchers and industry stakeholders.
Vedoucí práce: Heřman Kopkáně
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses